Fabrication and characterization of InP/InGaAs Metamorphic heterojunction bipolar transistors (HBTs) - Yang, Hong (2008)
High gain metamorphic InP/InGaAs/InP DHBTs (double heterojunction bipolar transistors) on GaAs substrate fabricated using complete NTU in-house process have been demonstrated in this investigation. DC and RF characterization of various MHBTs (metamorphic HBTs), including noise and power measurements, elevated temperature and current stress measurements, evaluation of thermal resistance, and performance comparison of devices grown by different growth techniques have been accomplished. Other important tasks completed include new device design and mask layout, and development of two-micron or less emitter width device process technology.